Strategi Pemasaran dalam Menarik Minat Konsumen pada Makanan Ringan Cimol Kressoy (Cimol Krenyess A Soy) - Eka Nurzanah (Bulletin of Community Engagement, 2024)
This study was aimed to determine the marketing strategy applied to Cimol Kressoy Snacks SMEs, especially the marketing mix. This study used a qualitative method, namely a case study that produces descriptive data as outlined in words. Using the data collection technique in this study, the author made a direct visit to Cimol Kressoy Snacks SMEs to conduct a personal interview with the owner. The result showed that the marketing strategy used by Cimol Kressoy Snacks SMEs was the 4P marketing mix consisting of product, price, place and promotion. The product strategy is in the form of determining the logo, creating the brand, label, the price strategy by providing relatively affordable prices, the place strategy in the form of being flexible in product delivery to distributors, and the promotion. Although there are obstacles to declining sales, Cimol Kressoy Snacks SMEs can still find solutions and alternatives, namely by maintaining cash flow, maximizing social media as a promotional medium and creating market accounts. The conclusion is that the marketing strategy used by Cimol Kressoy Snacks SMEs is quite good.